Maternal and procedural factors associated with estimated blood loss in second trimester surgical uterine evacuation: a retrospective cohort analysis. (August 2020) - Bridges, K.H.; Wolf, B.J.; Dempsey, A.; Ellison, W.B.; Williams, D.Y.; Wilson, S.H.
Highlights: Operative uterine evacuation is a common procedure despite restricted access. Bleeding risk factors have not been described in centers with <50 cases per year. Increased gestational age and surgical indication may increase bleeding risk. Transfusion and re-admission rates for bleeding were low in our center. Abstract: Background: Prior studies examining bleeding with uterine evacuation have focused on high-volume centers performing over 1100 procedures annually. The aim of this study was to examine associations between blood loss and patient and procedural characteristics in a center performing fewer than 50 procedures annually. Methods: This retrospective cohort study, with institutional review board approval, utilized procedural codes to identify patients undergoing uterine evacuation procedures between 14 weeks' and 24 weeks' gestational age across a 50-month period. The primary outcome was estimated blood loss; secondary outcomes were hemorrhage, transfusion and hospital re-admission. Associations between blood loss and other variables were examined using linear regression models. Results: Charts of 161 women met inclusion criteria. Median estimated blood loss was 400 mL (IQR 300 mL) with 37% of patients having blood loss of ≥500 mL. In univariate analyses, increased blood loss was associated with later gestational age ( P  <0.001) and pregnancy termination ( P  <0.001). In a multiple linear regression model, both remained significant. Each one-week increase in gestational age was associated with a 7.1% mean increase in estimated blood loss (95% CI 2.47% to 11.9%; P =0.003). Patients whose uterine evacuation was indicated for pregnancy termination had an 80.6% increase in blood loss compared with those with pre-operative fetal demise (95% CI 37.5% to 137.2%; P  <0.001). Rates of peri-operative transfusion and re-admission for bleeding were <4%. Conclusion: While blood loss may be greater in low volume centers, our transfusion and re-admission rates were low following second trimester uterine evacuation.